A trajetória do periódico científico na Fundação Oswaldo Cruz: perspectivas da Biblioteca de Ciências Biomédicas The trajectory of scientific periodicals at the Fundação Oswaldo Cruz: perspectives of the Biomedical Sciences Library - Jeorgina Gentil Rodrigues; Sandra Maria Osório Xavier Marinho (História, Ciências, Saúde: Manguinhos)
Descreve a formação do acervo de periódicos científicos da Biblioteca de Ciências Biomédicas da Fundação Oswaldo Cruz. Destaca a coleção de periódicos científicos raros, que se estende do século XVIII ao XX e contempla valiosos trabalhos na área das ciências biológicas e da saúde. Apresenta a criação da instituição por Oswaldo Cruz e a organização da biblioteca. Documenta o empenho da Biblioteca de Ciências Biomédicas em promover o acesso ao periódico científico em diferentes formatos tecnológicos. The article describes the formation of the scientific periodicals collection of the Fundação Oswaldo Cruz Biomedical Sciences Library. It highlights the collection of rare scientific periodicals that extends from the 18th century to the 20th and encompasses valuable works in the biological sciences and health fields. The work also includes the creation of the institute by Oswaldo Cruz and the organization of the Library and documents the efforts of the Biomedical Sciences Library to promote access to scientific periodicals in different technological formats.